Job insecurity, employability, and health: An analysis for Germany across generations - Steffen Otterbach; Alfonso Sousa-Poza (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2014)
In this paper, we use 12 waves of the German Socio-Economic Panel to examine the relationship between job insecurity, employability and health-related well-being. Our results indicate that being unemployed has a strong negative effect on life satisfaction and health. They also, however, highlight the fact that this effect is most prominent among individuals over the age of 40. A second observation is that job insecurity is also associated with lower levels of life satisfaction and health, and this association is quite strong. This negative effect of job insecurity is, in many cases, exacerbated by poor employability.
urn:nbn:de:bsz:100-opus-9758
Keywords: J21; J22; 330; job insecurity; employment; employability; well-being; health; Germany